2013
DOI: 10.1111/lam.12032
|View full text |Cite
|
Sign up to set email alerts
|

Sub-lethal concentrations of antibiotics increase mutation frequency in the cystic fibrosis pathogen Pseudomonas aeruginosa

Abstract: Approximately 80% of adult patients with cystic fibrosis (CF) become chronically infected with Pseudomonas aeruginosa and consequently require antibiotic therapy at intervals throughout their lives. Achieving lethal concentrations of antibiotics in the lung remains a challenge. Recent evidence from Escherichia coli and Staphylococcus aureus suggests that the generation of hydroxyl radicals by sublethal concentrations of antibiotics may induce mutagenesis and confer bacteria with resistance to a wide range of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 24 publications
1
40
2
Order By: Relevance
“…Additionally, oxidation of DNA and free nucleotides can induce mismatched pairing, mutagenesis, and DSBs (Cadet, 2003; Foti et al, 2012; Haghdoost et al, 2006). We detected significantly elevated rates of DSBs that support previous reports that detected higher mutagenesis rates and DNA damage during antibiotic exposure (Dwyer et al, 2012; Foti et al, 2012; Kohanski et al, 2010a; Méhi et al, 2014; Nair et al, 2013). …”
Section: Discussionsupporting
confidence: 91%
“…Additionally, oxidation of DNA and free nucleotides can induce mismatched pairing, mutagenesis, and DSBs (Cadet, 2003; Foti et al, 2012; Haghdoost et al, 2006). We detected significantly elevated rates of DSBs that support previous reports that detected higher mutagenesis rates and DNA damage during antibiotic exposure (Dwyer et al, 2012; Foti et al, 2012; Kohanski et al, 2010a; Méhi et al, 2014; Nair et al, 2013). …”
Section: Discussionsupporting
confidence: 91%
“…Due to location of the bacteria in zones where the concentration of systemically administered antibiotics are sub-optimal, the role of subinhibitory concentrations of antibiotics for the occurrence of bacterial heterogeneity has also been studied [230][231][232][233], showing that exposure to sub-MIC concentrations led to occurrence and selection of resistant bacteria to several classes of antibiotics unrelated to the drug of exposure, suggesting a general increase in mutability as mechanism.…”
Section: Paeruginosa Adaptation To the Cf Lung: Bacterial Heterogeneitymentioning
confidence: 98%
“…The immediate responses of P. aeruginosa to subinhibitory concentrations of ciprofloxacin have been investigated in several studies that reported enhancement in the frequency of mutation leading to carbapenem (especially meropenem) resistance (Tanimoto et al, 2008), reduction of swimming and swarming motilities (Linares et al, 2006) and increase in spontaneous mutation frequencies (Nair et al, 2013). Transcriptional responses of P. aeruginosa to subinhibitory and inhibitory concentrations of ciprofloxacin demonstrated the induction or repression of hundreds of genes (Brazas et al, 2007;Brazas & Hancock, 2005;Cirz et al, 2006).…”
Section: Introductionmentioning
confidence: 99%